Is There a Difference in The Life Skills of Students Who Participate in Sport and Non- Sports Extracurricular Activities ? - Ilmi Legismawati Pauzi; Mudjihartono; Agus Gumilar (Universitas Negeri Semarang, 2025)
Life skills are important abilities that help adolescents face various challenges in daily life, including social, emotional, and academic issues. This study aims to determine the differences in life skills levels between students participating in sports and non-sports extracurricular activities at Junior High School 26 Bandung. The study used a quantitative descriptive approach involving 7th and 8th grade students as a sample. Data collection was carried out using the Life Skills Scale for Sport (LSSS) instrument, which assesses eight aspects of life skills, such as teamwork, goal setting, time management, communication, leadership, and decision-making. The results of the analysis using an independent sample t-test showed that students participating in sports extracurricular activities had higher scores on aspects of teamwork, time management, interpersonal communication, social skills, and overall life skills. Several other aspects did not show significant differences, but in general, sports activities made a greater positive contribution to the development of student’s life skills. These findings confirm that involvement in sports activities not only improves fitness but also supports the formation of character and important skills needed by adolescent in everyday life.